The effects of epileptic seizures upon quality of life - Salgado,Priscila Camile Barioni (2009)
OBJECTIVE: understand the psychological considerations of the relationship between the effect of seizures upon the patients' perception of seizure control, depression, anxiety and quality of life (QoL). METHODS: 151 adult patients with epilepsy diagnosed for over two years were interviewed and responded the 31-Item Quality of Life in Epilepsy (QOLIE-31), the Trait Form of the State/Trait Anxiety Inventory (STAI II) and the Beck Depression Inventory (BDI). RESULTS: 45 patients were depressed (29.8%) and 29 (19.2%) had anxiety. Depression scores ranged from 0 to 49 (M=7.4; SD=8.9) and anxiety scores ranged from 19 to 69 (M=41.5, SD=11.9). Total QoL score was correlated to seizure control (p<0.001), perception of epilepsy control (p<0.001), anxiety (p<0.001), and depression (p=0.003). The perception of epilepsy control was correlated to seizure control (p<0.001), seizure frequency (p=0.001), anxiety (p<0.001) and depression (p<0.001). Seizure control was associated to anxiety (p=0.033) and depression (p<0.001). There was co-morbidity between anxiety and depression (p<0.001). CONCLUSION: This study highlights the importance of the seizure frequency and control to the evaluation of perception of epilepsy control and shows that anxiety and depression in epilepsy are predicted by seizure-related (seizure frequency and control) and psychosocial aspects (perception of control and QoL) together.